PELAKSANAAN DAKWAH JAMAAH TABLIGH DALAM MEMBINA KELUARGA SAKINAH - Taqwatul Uliyah; M. Nasor M. Nasor; M. Damrah Khair; Hasan Mukmin (Postgraduate State Islamic Institute (IAIN) Metro, 2019)
Marriage is one of the cycles of human life that gives birth to new social status and gives rise to new roles both of the spouse and the spouse's relatives. Once the importance of the meaning of a marriage in society because through marriage causes a family relationship. The husband and wife bear the noble obligation to uphold the household which is the basic joint of the community structure. The family is fostered by a pair of people who have agreed to navigate together with sincerity and faithfulness, based on the beliefs that are confirmed through marriage, and is affixed with love to complement each other and improve themselves in the direction of Allah's blessing. Allah SWT intentionally fosters affection into the hearts of each partner, so that harmony and peace can occur in fostering a household. The existence of a marriage bond is expected to create a sense of responsibility to foster domestic life, especially between husband and wife in addition to establishing a familial relationship between the two parties. However, not always life and relationships between husband and wife run smoothly, waves and household storms sometimes happen to them.